Cotton Agriculture in Turkey and Worldwide Economic Impacts of Turkish Cotton. Issue 15 (23rd November 2022) - Tokel, Dilek; Dogan, Ilhan; Hocaoglu-Ozyigit, Asli; Ozyigit, Ibrahim Ilker
ABSTRACT: Cotton is a product that provides wealth for humanity with its widespread and compulsory usage, and alongside creating employment opportunities in the producer countries. Due to the availability of suitable land for agriculture, seven countries including Turkey produce close to 80% of cotton worldwide. The average cotton yield in Turkey is above the world average, placing the country close to first place among the major producing countries. On the other hand, Turkey is one of the main countries engaged in organic cotton production by using only non-transgenic seeds and therefore, its cotton as a brand is registered as "GMO Free Turkish Cotton". This provides a privileged position to the country as "the only country in the world producing GMO-free cotton". Also, the Turkish textile industry is a driving sector for the country in terms of producing high-quality products, bringing foreign exchange to the country and creating a large labor-intensive workforce for the country. In this study, the state of cotton affairs was discussed in detail using relevant data along with its trade and importance in the textile industry in the world and Turkey.